2020
DOI: 10.1186/s12896-020-00629-8
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification (LAMP) reaction as viable PCR substitute for diagnostic applications: a comparative analysis study of LAMP, conventional PCR, nested PCR (nPCR) and real-time PCR (qPCR) based on Entamoeba histolytica DNA derived from faecal sample

Abstract: Background This study reports the analytical sensitivity and specificity of a Loop-mediated isothermal amplification (LAMP) and compares its amplification performance with conventional PCR, nested PCR (nPCR) and real-time PCR (qPCR). All the assays demonstrated in this study were developed based on Serine-rich Entamoeba histolytica protein (SREHP) gene as study model. Results A set of SREHP gene specific LAMP primers were designed for the specific detection of Entamoeba histolytica. This set of primers record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 29 publications
(42 reference statements)
0
46
0
1
Order By: Relevance
“…S25 ). Literature reports vary concerning the effectiveness of betaine in LAMP reactions ( Foo et al, 2020 ; Zhou et al, 2014 ); however, evidence exists indicating that betaine reduces oxidative damage, and we, therefore, included it in our formulation ( Willingham et al, 2020 ). Trehalose has been reported to act as a protein stabilizer by resisting dehydration when drying ( García-Bernalt Diego et al, 2019 ; Hayashida et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…S25 ). Literature reports vary concerning the effectiveness of betaine in LAMP reactions ( Foo et al, 2020 ; Zhou et al, 2014 ); however, evidence exists indicating that betaine reduces oxidative damage, and we, therefore, included it in our formulation ( Willingham et al, 2020 ). Trehalose has been reported to act as a protein stabilizer by resisting dehydration when drying ( García-Bernalt Diego et al, 2019 ; Hayashida et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Isothermal NAATs have unique applications in POC COVID-19 diagnostics, providing fast results without need for specialized equipment ( Foo et al., 2020 ; Yan et al., 2020a ). Practical considerations.…”
Section: Nucleic Acid Amplification Testsmentioning
confidence: 99%
“…This report, along with previously mentioned studies, confirmed the LAMP technique's advantages over the previous complex molecular methods in the rapid and sensitive detection of pathogenic microorganisms. 93…”
Section: Loop-mediated Isothermal Amplification (Lamp)mentioning
confidence: 99%